PENGEMBANGAN EVALUASI PELAKSANAAN PENDIDIKAN ISLAM - Fatimah Uri; Saputra, Decky (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Evaluation in Islamic education plays a strategic role not only in measuring learning outcomes but also in shaping students’ character and spiritual integrity. This article aims to examine evaluation approaches and strategies aligned with Islamic values while offering a new integrative conceptual model. Employing a descriptive-qualitative approach through literature review and supported by field-based practices in Islamic schools and madrasahs, this study finds that ideal evaluation in Islamic education must address three domains: cognitive, affective, and psychomotor. These are best assessed through a combination of quantitative, qualitative, and holistic approaches. Current evaluation practices—such as value-based assessment, technology integration, and authentic assessment—have shown potential in Islamic educational institutions, though their implementation remains inconsistent. As a conceptual contribution, this article proposes the Integrative-NTA Model of Islamic Educational Evaluation (Values, Technology, Authentic Assessment), which frames evaluation as a transformative process grounded in Islamic ethics. The model provides a comprehensive, context-sensitive framework that bridges classical evaluation theory with the demands of contemporary Islamic education. It offers practical guidance for educators, curriculum developers, and policymakers to construct meaningful, value-oriented assessment systems.